(untitled) (Sociologisk Forskning, 2001)
Democracy and national imagination: assumptions of identity and belonging in studies on democracy Until recently, questions of migration and ethnic relations were hardly discussed within political research on democracy. Categories such as ‘nation’, ‘culture’ and ‘ethnicity’ have been taken for granted, looked upon as self-evident and independent factors. Research on democracy has generally been permeated by what might be called ‘national imagination’, a nation-state-centred and ethnocentric paradigm, where homogenous national belongings and national borders have been assumed, advocated and legitimated as fundamental elements of political life. Within this kind of paradigm, ethnic minorities have been represented as fundamentally ‘different’ from the ‘norm ality’, that is ethnic majority populations. In general, phenomenon such as mix of cultures, border-crossing and migration have been portrayed as in itself abnormal, disrupting and problematic features of political life. The conclusion in the article is that it is necessary to question and to challenge hegemonic conceptions of identity and belonging in research on democracy.